Time course of anaerobic and aerobic energy expenditure during short-term exhaustive running in athletes - Nummela, A.; Rusko, H. (International Journal of Sports Medicine, 1995)
The aim of the present study was to investigate the time course of aerobic and anaerobic energy yield during supramaximal exhaustive running on the treadmill in sprint and endurance athletes. In addition, the relationships between O2 deficit, excess post-exercise O2 consumption (EPOC) and peak post-exercise blood lactate concentration (peak BLa) values were examined, Oxygen uptake during the exhaustive run and 15 min recovery period was measured using a breath-by-breath method. The accumulated O2 deficit was calculated by an extrapolation procedure. Total running time was the same for eight male sprint runners (49.5 +/- 6.0s) and for six male endurance athletes (49.4 +/- 5.3 s). The sprint group had significantly higher O2 deficit (p < 0.01) during the run as well as higher peak BLa (p < 0.05) and EPOC (p < 0.01) after the run than the endurance group. The relative contribution of anaerobic energy yield decreased from 80% to 60% during the first 15 s of the exhaustive run in both groups. The VO2 peaked and was almost unchanged from 25th to 40th s of the run in both groups, although only 79% of their VO2max was attained. The relative contribution of aerobic energy yield was significantly higher (p < 0.05) in the endurance (54-63%) than in the sprint group (43-47%) during the second half of the run. No correlation was found between the O2 deficit and EPOC but peak BLa correlated significantly (p < 0.05) with the O2 deficit (r = 0.53) and EPOC (r = 0.53). In conclusion, the energy release of the sprint and endurance athletes was different only during the second half of the exhaustive supramaximal run, when the sprinters used more the anaerobic and endurance athletes aerobic pathways for energy production.